(untitled) (Medico Legal Update, 2020)
The development of human trafficking has changed to happen to the kinds of people who are disadvantaged, such as woman and children. The trafficking of woman and children is one of the bad forms treatment from the exploitation activity which is faced by woman and children. Trafficking is included as a crime and a human rights violation. Indonesia itself is a region where woman and children trafficking happens, either as country of the victims’ origin or as a transit country. Some regions in Indonesia are estimated as targets of border countries’ crime syndicate activities which organize woman and children trafficking. This research analyzes the women and children trafficking in Jember Regency in the perspectives of law and health.